Hydrothermal Synthesis of Nanocrystalline Zeolite using Clear Solution - Syaifullah Muhammad (Sriwijaya International Seminar on Energy-Environmental Science and Technology, 2014)
Nano size particles such as nanocrystalline zeolites have unique properties relative to conventional micrometer sized zeolite crystals. The reduction of particle size to the nanometer scale leads to substantial changes in properties of zeolite which make them as promising materials for many applications. Nanocrystalline zeolite A, silicate-1 and ZSM-5 were successfully synthesiszed at temperature of 80-1500C using clear solution in the presence of organic templates. Values of 1.46, 3.06, 4.59 and 6.79 are effective Si/Al ratio to synthesis LTA zeolite. Further, high Si/Al ratio of 30, 40 and 60 were used for ZSM-5 synthesis. The product could be obtained at 1-5 day for zeolite A and ZSM-5 while silicate-1 (aluminum free) could be obtained at 5-9 day. It is proved that zeolite yields increased with increasing temperature, time, Si/Al ratio and organic template. Moreover, TEOS and Ludox LS as silica sources in the silicate-1 synthesis were found to influence the particle size. TEOS makes the zeolite particle smaller than Ludox LS. Two stage synthesis conducted on silicate-1 crystallization could decrease time and increase yield. However it is found that the average particle size was slightly higher than that in one-stage synthesis.